Issues in international exchange and payments systems (IMF WashingtonUS, 1995)
Focuses on progress toward current account and capital account convertibility. Looks at evolving roles of exchange rate regimes and bilateralism and regionalism in cross-border payments. Highlights the implications for the IMF's technical assistance and issues that arise in the context of exchange system developments.
DC